Association of TCRαβ+ double-negative T cells with the response to glucocorticoids in pediatric patients with immune thrombocytopenia - Chen, Hui; Xie, Xingjuan; Ma, Jingyao; Fu, Lingling; Wu, Runhui; Chen, Zhenping (Frontiers in Immunology, 2025)
ObjectivesPediatric primary immune thrombocytopenia (ITP) is an acquired autoimmune disease that can be partially restored by glucocorticoids. TCRαβ+CD4−CD8− double negative T cells (TCRαβ+DNT) has been linked to the pathophysiology of ITP; however, the role of TCRαβ+DNT in response to high-dose dexamethasone (HD-DXM) is unclear. In this study, we aimed to explore the alteration in TCRαβ+DNT in ITP and the effect of HD-DXM on this subset.Materials and methodsPediatric patients (aged <18 years) newly diagnosed with ITP were recruited for this retrospective study. Th1, Th17, Treg, and TCRαβ+DNT levels were measured by flow cytometry using specific antibodies. All patients received HD-DXM treatment and underwent periodic outpatient follow-up for 2-6 months. Patients were divided into the overall response (OR) and no response (NR) groups according to their responses to HD-DXM treatment.ResultsWe enrolled 130 pediatric patients with ITP (OR, 95 cases; NR, 35 cases) and 50 age- and sex-matched healthy controls. Compared with Th17-to Treg, Th17, and Th1, univariate analysis identified that the proportion of TCRαβ+DNT at baseline was more effective in predicting the response to HD-DXM (P<0.05). A significantly increased frequency of TCRαβ+DNT was found in patients with ITP compared to healthy controls (percentage of T cells: 1.31% vs. 1.00%, P<0.0001; percentage of lymphocytes: 0.76% vs. 0.68%, P=0.010). Patients in the NR group had a higher percentage of TCRαβ+DNT than the OR at the initial diagnosis (TCRαβ+DNT/T: 1.52% vs. 1.30%, P<0.01; TCRαβ+DNT/Lym: 0.84% vs. 0.72%, P<0.01). After treatment with HD-DXM, the elevated TCRαβ+DNT was effectively reduced in the OR group, but not in the NR group (TCRαβ+DNT/T: P<0.05; TCRαβ+DNT/Lym: P=0.001; TCRαβ+DNT counts: P<0.01).ConclusionsTCRαβ+DNT appears to play a significant role in the pathogenesis of pediatric ITP and may be involved in the immune response to HD-DXM. The correction of elevated TCRαβ+DNT in patients who respond to HD-DXM may provide a novel insight for immune therapy in pediatric ITP.